UPP mediated Diabetic Retinopathy via ROS/PARP and NF-ΚB inflammatory factor pathways. - . Luo, D.-W; Zheng, Z.; Wang, H.; Fan, Y.; Chen, F.; Sun, Y.; Wang, W.-J.; Sun, T.; Xu, X. (Current Molecular Medicine, 2015)
Diabetic retinopathy (DR) is a leading cause of blindness in adults at working age. Human diabetic retinopathy is characterized by the basement membrane thick, pericytes loss, microaneurysms formation, retina neovascularization and vitreous hemorrhage. To investigate whether UPP activated ROS/PARP and NF-ΚB inflammatory factor pathways in Diabetic Retinopathy, human retinal endothelial cells (HRECs) and rats with streptozotocin-induced diabetes were used to determine the effect of UPP on ROS generation, cell apoptosis, mitochondrial membrane potential (ΔΨm) and inflammatory factor protein expression, through flow cytometry assay, immunohistochemistry, Real-time PCR, Western blot analysis and ELISA. The levels of ROS and apoptosis and the expressions of UPP (Ub and E3) and inflammatory factor protein were increased in high glucose-induced HRECs and retina of diabetic rats, while ΔΨm was decreased. The UPP inhibitor and UbshRNA could attenuate these effects through inhibiting the pathway of ROS/PARP and the expression of NF-ΚB inflammatory factors, and the increased UPP was a result of high glucose-induced increase of ROS generation and NF-ΚBp65 expression, accompanied with the decrease of ΔΨm. Clinical study showed the overexpression of UPP and detachment of epiretinal membranes in proliferative DR (PDR) patients. It has been indicated that the pathogenic effect of UPP on DR was involved in the increase of ROS generation and NF-ΚB expression, which associated with the ROS/PARP and NF-ΚB inflammatory factor pathways. Our study supports a new insight for further application of UPP inhibitor in DR treatment.
Keywords: PARP